AN EVALUATION STUDY OF THE COMPETENCY OF PERFORMANCE OF THE OUTPUTS OF COLLEGES OF PHYSICAL EDUCATION AND SPORTS SCIENCES FROM THE OPINION OF MIDDLE SCHOOL ADMINISTRATIONS - Shakir, Salah Wahab (International Journal of Psychosocial Rehabilitation, 2020)
This study assesses performance competency among the graduates of the colleges of physical education and sports sciences and developing a measuring tool for the performance competency that enable the researcher to achieve objective results. A descriptive, surveying method was used on (324) middle school managers who were Method: purposively selected from Al-Karkh side in Baghdad governorate. The study results revealed that teachers can know their tasks and plan their lessons, but they have a weakness in following-up the applications of physical education lessons according to their educational and learning goals, most teachers have a good body of knowledge about the training tools to improve students’ performance. However, they do not excel arbitrating sport activities and competitions, most teachers have a personality belovedby students, and they sometimes act individually, do not listen to others’ opinions, teachers areable to consolidate positive relationships and perform multiple tasks.